Comparative evaluation of shear bond strength between fifth, sixth, seventh, and eighth generation bonding agents: An In Vitro study - A Sri Ganesh (Wolters Kluwer Medknow Publications, 2020)
Aim: To evaluate and compare the shear bond strength of composite resin to dentin using eighth generation dental adhesive (G-Premio Bond) with fifth, sixth, and seventh generation dentin adhesives. Materials and Methods: A total of 64 freshly extracted non-carious, intact human premolar teeth were selected. Class V cavity was prepared by using high speed hand piece. The prepared samples were randomly divided into four experimental groups (n = 16). Group I: Adper single Bond 2 [fifth generation] (ASB-5), Group 2: Clearfil SE [sixth generation] (CSE-6), Group 3: Single Bond Universal [seventh generation] (SBU-7), Group 4: G-Premio Bond [eighth generation] (GPB-8). Bonding agents were applied according to the manufacturer's instructions and light cured. Then, the Nano composite Filtek Z350 was placed in a two layer increment using Teflon Jig (2 × 2 × 2 mm) and was light-cured for 40 s. Shear bond strength was tested by a universal testing machine. This study was carried out by using Tukey HSD post-hoc test where P ≤ 0.05 was considered as a statistical significant. Results: The highest value of shear bond strength was obtained from G-Premio Bond (eighth generation) showed statistically significant difference when compared to seventh generation bonding agent. However, there is no statistical significant difference between eighth and fifth, sixth generation. Conclusion: The study concluded the G-Premio Bond (eighth generation) showed effective shear bond strength than other bonding agents. This bonding agent is compatible with self-etch without use of primer which gives highly long lasting esthetic, wear resistant, and it is ideal for hypersensitive tooth.